THE FRACTAL NATURE OF THE COUNTRY OF ORIGIN EFFECT - EXPLORING 50 YEARS OF COO RESEARCH - Tamas, Anca (European Scientific Journal, ESJ, 2015)
Purpose-the aim of the paper is to identify the main research avenues in the past 50 years of country of origin research and to reveal the fractal nature of the country of origin effect. Design/methodology/approachsystematic research of the relevant studies regarding country of origin; critical literature review; identifying fractal patterns of the country of origin effect. Findings-COO effect is a complex structure, highly sensitive to initial condition, similar to fractals; the COO effect is self-repeated, showing irregularity in every detail and impossible to be described by regular shapes or theories; the COO dimension is fractional due to the fractal nature of the COO effect. Practical implications-the practitioners find the COO effect for a specific product of a specific country in specific conditions is of high interest. Originality/value-the fractal nature of the COO effect might explain some of the contradictory findings in the past studies.